Two new Dismodix Townes (Hymenoptera, Ichneumonidae, Cryptinae) with an exceptionally broad occipital carina - Supeleto, Fernanda A.; Aguiar, Alexandre P. (Zootaxa, 2024)
Dismodix colai sp. nov., from a reforested legal reserve of Atlantic Forest in southeastern Brazil, and D. gladiata sp. nov., from central Brazil, are described and illustrated. Each new taxon is compared with similar species from both Dismodix Townes and the related Acerastes Cushman. Both species can be separated from all others within each genus by having the occipital carina distinctly widened.